2018
DOI: 10.1523/jneurosci.1163-18.2018
|View full text |Cite|
|
Sign up to set email alerts
|

A Multicomponent Neuronal Response Encodes the Larval Decision to Pupariate upon Amino Acid Starvation

Abstract: Organisms need to coordinate growth with development, particularly in the context of nutrient availability. Thus, multiple ways have evolved to survive extrinsic nutrient deprivation during development. In Drosophila, growth occurs during larval development. Larvae are thus critically dependent on nutritional inputs; but after critical weight, they pupariate even when starved. How nutrient availability is coupled to the internal metabolic state for the decision to pupariate needs better understanding. We had e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 99 publications
1
25
0
Order By: Relevance
“…IP 3 -mediated calcium release from the IP 3 R in the presence of Itpr DN , was tested on previously characterised glutamatergic interneurons in the larval ventral ganglion known to respond to the muscarinic acetylcholine receptor (mAChR) ligand Carbachol. These neurons can be marked with a GAL4 strain ( vGlut VGN6341 ; Jayakumar et al, 2016 ; Jayakumar et al, 2018 ). Changes in cytosolic calcium were measured by visualising Ca 2+ dependent fluorescence changes of a genetically encoded Ca 2+ sensor GCaMP6m ( Chen et al, 2013 ) in ex vivo preparations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IP 3 -mediated calcium release from the IP 3 R in the presence of Itpr DN , was tested on previously characterised glutamatergic interneurons in the larval ventral ganglion known to respond to the muscarinic acetylcholine receptor (mAChR) ligand Carbachol. These neurons can be marked with a GAL4 strain ( vGlut VGN6341 ; Jayakumar et al, 2016 ; Jayakumar et al, 2018 ). Changes in cytosolic calcium were measured by visualising Ca 2+ dependent fluorescence changes of a genetically encoded Ca 2+ sensor GCaMP6m ( Chen et al, 2013 ) in ex vivo preparations.…”
Section: Resultsmentioning
confidence: 99%
“…The cellular mechanism(s) by which IP 3 /Ca 2+ signals regulate neuronal excitability probably vary among different classes of neurons. In addition to the direct activation of Ca 2+ -dependant enzymes such as CamKII, previous reports have shown that knock-down of the IP 3 R in Drosophila larval neurons alters their expression profile and specifically affects the expression of several membrane localised ion-channels ( Jayakumar et al, 2018 ). Reduced translation of proteins due to IP 3 R knockdown has also been demonstrated in peptidergic neurons ( Megha and Hasan, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, during mid-third instar Class IV multidendritic nociceptive ppk peripheral neurons react to the loss of environmental arginine via Slif. Then, they activate glutamatergic neurons in the ventral chord, which in turn stimulate Dilp2 release by IPCs [ 51 , 52 ]. Imaginal discs seem also to be sensitive to the presence of nutrients including amino acids via the activity of the tumor suppressor PTEN (phosphatase and tensin homolog deleted on chromosome 10).…”
Section: Discussionmentioning
confidence: 99%
“…dependant enzymes such as CamKII, previous reports have shown that knock-down of the IP 3 R in Drosophila larval neurons alters their expression profile and specifically affects the expression of several membrane localised ion-channels (Jayakumar et al, 2018). Reduced translation of proteins due to IP 3 R knockdown has also been demonstrated in peptidergic neurons (Megha & Hasan, 2017).…”
Section: Intracellular Ca 2+ Signaling and Neuronal Excitabilitymentioning
confidence: 97%